Homo deus : a brief history of tomorrow - Harari, Yuval Noah, 1976- (London : Vintage, 2017)
As our gods take a back seat, and Homo Sapiens becomes Homo Deus, what are we going to do with ourselves? How do we set the agenda for our own future without pushing our species - and the rest of the world - beyond its limits? This book examines the implications of our newly upgraded condition, from our dogged pursuit of status and happiness to our constant quest to overcome death by pushing the boundaries of science. It explores how Homo Sapiens conquered the world, our creation of today's human-centred environment, our current predicament and our possible future. And, above all, he asks the fundamental questions: Where do we go from here? And how will we protect this fragile world from our own destructive powers?
Includes bibliographical references (pages [463]-493) and index.
Keywords: Civilization, Modern -- 21st century; Science and civilization; Future, The; Human beings -- History